Makna Takfîr Pemimpin bagi Kaum Salafi - Slamet Muliono (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2011)
This article provides one of Salafi’s views about takfîr against state leaders. So far, Islamic da‘wah movements have asserted that takfîr is allowed to find and point out the best leader who inclines to implement Islamic doctrines within a nation-state context. Takfîr, in the view of Islamic da‘wah movements, has emerged as a result of the leader’s reluctance or failure to implement the Islamic sharîa within the nation-state’s life. However, in the view of Salafi groups, takfîr through coup d’état would likely obliterate the state order. The Salafi groups view that this sort of takfîr, which aims to replace leadership through coup d’état, was Khawârij’s ideology. Nevertheless, the Salafi groups emphasize that there would be no guaranty for better leadership after coup d’état. Even so, it has often led to the emergence of worse leadership, which creates social disorder.